Hierarchical planning for pharmaceutical preparedness in the event of disasters: A Delphi consensus study - Lingga Ikaditya; Zulfan Zazuli; Yosi Agustina Hidayat; I Ketut Adnyana (Pharmacia)
Cross-sector collaboration is a strategy employed in the realm of pharmaceutical disaster preparedness. The present study aims to integrate the roles of all stakeholders in the collaboration function through hierarchical planning. The Delphi method was employed as the primary research approach, specifically in the context of an expert consensus study. This method involved conducting a three-round Delphi survey, encompassing seven experts. The results of each round yielded an Interquartile Range (IQR) ≤20, indicating a strong consensus among experts in assessing the parameters. Subsequently, these parameters were categorized based on hierarchical planning: strategic (8 parameters), tactical (9 parameters), and operational (13 parameters). The Delphi process was successful in achieving a consensus from diverse perspectives on collaborative efforts in pharmaceutical preparedness in the event of a disaster. These findings serve as a policy framework for defining stakeholder authority and responsibilities within the disaster mitigation cycle, particularly in the pharmaceutical sector.